Commercial release of genetically engineered insect resistant cowpea in Nigeria informed by ex ante modelling and capacity building conducted by IFPRI's Program for Biosafety Systems - CGIAR Research Program on Policies, Institutions, and Markets (2019)
The Nigerian authorities approved for general release the genetically engineered pod borer resistant cowpea in 2019. Support from the Program for Biosafety Systems included over a decade of institutional and individual capacity building on regulatory issues and more recently led to a credible and robust ex ante economic assessment of insect resistant cowpea.